The Rights of The Stateless and Their Problems in State of Kuwait - Alhajri, Saad obaid (Journal of Economic, Administrative and Legal Sciences, 2021)
This study deals with an issue that is not specific to the nationality of the State of Kuwait. This issue is considered one of the most important issues in the country of Kuwait. It about depriving the stateless of political and social rights. In this research, we will address the human and social rights that they enjoy and which they may be deprived of. The research also aims to explain the problematic nature of this issue to the society if it is not resolved by the appropriate solution. The importance of this research enables us to know the solutions of the issue, and discussed these solutions by descriptive analytical to come up with a radical solution that ends the suffering of that category. Keywords: Rights, Problematic, Undetermined Nationality.